Changes within Continuity: An Analysis of Recent Brazilian Foreign Policy (1990-2010) - Esteban Actis (Íconos)
The current article proposes analyzing the recent orientation of Brazilian foreign policy (1990-2010) by highlighting and illuminating the elements of change and continuity that President Lula’s arrival to power entailed regarding the foreign activities of Brazil. Despite maintaining – under another format – the principle of autonomy in external links, Lula’s government put forth a new foreign policy orientation. Given the theoretical proposal that neoclassical realism offers, in this article it is maintained that while Brazil’s place in the international structure determines and constrains foreign options, these options do not translate homogeneously at the level of the state unit. The particular beliefs and perceptions of policy makers are fundamental for understanding the particular direction of foreign policy.